Cushing’s syndrome during pregnancy - two case reports - Cholekho, Sumita; Liu, Yuke; Tan, Huiwen (Frontiers in Endocrinology, 2024)
Cushing's syndrome (CS) during pregnancy is a rare endocrine disorder characterized by hypercortisolism, which is significantly associated with maternal-fetal complications. Despite its rarity, CS during pregnancy may be related to a high risk of complications for both the mother and fetus.The aim of the present case study is to update the diagnostic approach to CS during pregnancy and the therapeutic strategies for this medical condition to minimize maternal-fetal complications.Here, we present two cases of CS in pregnant women, one of whom had twins. Typical clinical symptoms and signs of hypercortisolism developed at the beginning of pregnancy. The plasma cortisol diurnal rhythm of the pregnant patient was absent. CS was confirmed by cortisol and adrenocorticotropic hormone (ACTH) assessment, as well as imaging examination.We investigated the changes in the hypothalamic-pituitary-adrenal axis during normal pregnancy and the etiology, diagnosis and treatment of CS during pregnancy. The aim of the present case study is to update the diagnostic approach to CS during pregnancy and the therapeutic strategies for this medical condition to minimize maternal-fetal complications.Due to the associated risks of laparoscopic adrenalectomy,it is uncertain whether this treatment significantly decreases overall maternal mortality.Additional observational research and validation through randomized controlled trials (RCTs) are required. We advise that CS in pregnant women be diagnosed and treated by experienced teams in relevant departments and medical centers.